(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
The high rise in the exploration and usage of petroleum products have led to widespread contamination in the environment. Thence, the continuous search for microorganisms with the potential to mineralize these pollutants is necessary. This study was conducted to isolate, identify and determine the diesel degradation potential of bacteria from oil-contaminated soil collected from three filling stations in Azare, Katagum LGA, Bauchi State, Nigeria. The diesel degrading bacteria were identified using standard protocols. The isolates were screened spectrophotometrically for their potential to utilize 1% diesel (v/v) as their sole carbon and energy source and the best candidate was used for determining the effect of diesel concentration on its biodegradation. The results revealed the presence of three bacterial species including Pseudomonas aeruginosa, Pseudomonas putida and Bacillus subtilis. P. Putida showed the highest diesel degradation at 120 h with an absorbance of 2.27±0.03 at 600 nm followed by P. aeruginosa (2.23±0.03) and Bacillus subtilis. The best degradation was observed at 1% diesel concentration (v/v) followed by 2% and the least was recorded at 3% with the absorbance of 2.40±0.00, 2.27±0.03 and 2.20±0.00 respectively. The detection of these potential degraders is crucial in the light of the lingering search for efficient hydrocarbon degraders for efficient bioremediation since their degrative capability could be enhanced for deployment in the bioremediation of diesel-contaminated environments.